ENT 530 Social Media Portfolio: Urban Leaves / Wan Anis Amalin Wan Mohammad Azhar - Wan Mohammad Azhar, Wan Anis Amalin (2020)
Urban Leaves is a business that is selling real indoor plants. Urban Leaves business has been registered in Go e-Commerce portal, so it is a well-established business in Malaysia. The product of this business is indoor plants by the suppliers and it is located at No. 88, Jalan Meranti 3, Meranti, Bandar Hillpark, Puncak Alam, 42300 Selangor. As plants can give many benefits for us as humans, this business has set their own vision and mission. The vision is to be the leading indoor plants company with variety of plants, meanwhile the missions are to enrich our clients’ health and environment with the plants, to ensure all people know that putting plants in home is important and to encourage more people to love the natural creatures on the earth. Urban Leaves provides 12 different types of plants suitable for house, living room, dining room, offices and others with affordable prices and different sizes of plants. Then, this business can be reached in Facebook social media with the page named Urban Leaves Store. Currently, the page has 157 likers and followed by 163 people. The page contained by seven teasers about the new products and promotions and 16 Hard Sell posts about different products to attract many customers to buy the products immediately. The Hard Sell posts explained the details of the plant’s types with their own benefits and the seller provided the prices in the copywriting. The prices help the customers to calculate their own budget and they can make fast decision. Urban Leaves Store Facebook Page also contains 16 Soft Sell posts about plants knowledge and attract many audiences engage with this indoor plant business. The Soft Sell posts may help the new plants lover in taking care the plants in the right way. Also, there are 16 frequency of posting that will help the audience know that the seller is active in the Facebook and they may get instant replies if they ask about the plants. Lastly, Urban Leaves is also looking forward to improve and grow the business in the future. They are planning to gain and attract many customers by the interesting posts in Facebook with beautiful pictures, videos and the copywriting. They are looking forward to make many promotions and offers to make the customers feel happy and excited with the products and also build a good relationship with the seller. The vision and mission of Urban Leaves also need to be accomplished so that the business can be succeed and beneficial for the seller and the customers.